Lenvatinib Combined With Transarterial Chemoembolization as First-Line Treatment for Advanced Hepatocellular Carcinoma: A Phase III, Randomized Clinical Trial (LAUNCH). Issue 1 (1st January 2023) - Peng, Zhenwei; Fan, Wenzhe; Zhu, Bowen; Wang, Guoying; Sun, Junhui; Xiao, Chengjiang; Huang, Fuxi; Tang, Rong; Cheng, Yu; Huang, Zhen; Liang, Yuchuang; Fan, Huishuang; et al.
Abstract : PURPOSE: Lenvatinib (LEN) is a first-line therapy for patients with advanced hepatocellular carcinoma (HCC); however, it has shown modest survival benefits. Therefore, we aimed to compare clinical outcomes of LEN combined with transarterial chemoembolization (LEN-TACE) versus LEN monotherapy in patients with advanced HCC. MATERIALS AND METHODS: This was a multicenter, randomized, open-label, parallel group, phase III trial. Patients with primary treatment-naive or initial recurrent advanced HCC after surgery were randomly assigned (1:1) to receive LEN plus on-demand TACE (LEN-TACE) or LEN monotherapy. LEN was initiated within 3 days after random assignment (initial dose: 12 mg once daily for patients ≥ 60 kg; 8 mg once daily for patients < 60 kg). TACE was initiated one day after LEN initiation. The primary end point was overall survival (OS). RESULTS: Between June 2019 and July 2021, a total of 338 patients underwent random assignment at 12 centers in China: 170 to LEN-TACE and 168 to LEN. At a prespecified event-driven interim analysis after a median follow-up of 17.0 months, the median OS was significantly longer in the LEN-TACE group (17.8 v 11.5 months; hazard ratio, 0.45; P < .001). The median progression-free survival was 10.6 months in the LEN-TACE group and 6.4 months in the LEN group (hazard ratio, 0.43; P < .001). Patients in the LEN-TACE group had a higher objective response rate according to the modified RECIST (54.1% v 25.0%, P < .001). Multivariable analysis revealed that portal vein tumor thrombus and treatment allocation were independent risk factors for OS. CONCLUSION: The addition of TACE to LEN improves clinical outcomes and is a potential first-line treatment for patients with advanced HCC.